Proposed Guidelines for Improving Local Residents Participation on Sustainable Tourism Development: The Case of Tambon Chalong, Amphur Muang, Changwat Phuket - Varaporn Choosri (Prince of Songkla University, 2011)
Thesis (M.B.A., Hospitality and Tourism Management)--Prince of Songkla University, 2010